Fructose Induces Visceral Adipose Tissue Inflammation and Insulin Resistance Even Without Development of Obesity in Adult Female but Not in Male Rats - Kovačević, Sanja; Brkljačić, Jelena; Vojnović Milutinović, Danijela; Gligorovska, Ljupka; Bursać, Biljana; Elaković, Ivana; Djordjevic, Ana (Frontiers in Nutrition, 2021)
Introduction: Obesity and related metabolic disturbances are frequently related to modern lifestyle characterized by excessive fructose intake. Visceral adipose tissue (VAT) inflammation has a central role in the development of insulin resistance, type 2 diabetes (T2D) and metabolic syndrome. Since sex-related differences in susceptibility and progression of metabolic disorders are not yet fully understood, our aim was to examine inflammation and insulin signaling in VAT of fructose-fed female and male adult rats. Methods: We analyzed effects of 9-week 10% fructose-enriched diet on energy intake, VAT mass and histology and systemic insulin sensitivity. VAT insulin signaling and markers of VAT inflammation and antioxidative defense status were also evaluated. Results: Fructose diet had no effect on VAT mass and systemic insulin signaling in female and male rats, while it raised plasma uric acid, increased PPARγ level in the VAT and initiated development of distinctive population of small adipocytes in females. Also, adipose tissue insulin resistance, evidenced by increased PTP1B and insulin receptor substrate 1 (IRS1) inhibitory phosphorylation and decreased Akt activity, was detected. In addition, fructose stimulated nuclear accumulation of NFκB, increased expression of proinflammatory cytokines (IL-1β, IL-6 and TNFα) and protein level of macrophage marker F4/80, superoxide dismutase 1 and glutathione reductase. In contrast to females, fructose diet had no effect on plasma uric acid and VAT inflammation in male rats, while less prominent alterations in VAT insulin signaling were observed. Conclusion: Even though dietary fructose did not elicit changes in energy intake and led to obesity in females, it initiated proliferation of small-sized adipocytes capable of further fat storage. In contrast to males, this state of VAT was accompanied with enhanced inflammation, which most likely contributed to the development of insulin resistance. The observed distinction could possibly originate from the sex-related differences in uric acid metabolism. Our results suggest that VAT inflammation could precede obesity and start even before measurable increase of VAT mass, making it a silent risk factor for development of T2D. Our results emphasize that adipose tissue dysfunction, rather than its simple enlargement, could significantly contribute to the onset and development of obesity and related metabolic disorders.